Medullary thyroid carcinoma: biology, management, and treatment of sporadic and hereditary MTC - Raue, Friedhelm; Frank-Raue, Karin (Springer Nature Switzerland, 2025)
What is new? -- Thyroid C-Cell Biology and Oncogenic Transformation -- Histopathology of C cells and medullary thyroid carcinoma -- Epidemiology and clinical presentation of Medullary Thyroid Carcinoma -- Medullary thyroid carcinoma: Imaging -- Calcitonin as a Biomarker for Medullary Thyroid Carcinoma -- Hereditary Medullary Thyroid Cancer, Genotype phenotype correlation -- Pheochromocytomas in Multiple Endocrine Neoplasia type 2 -- Primary hyperparathyroidism in Multiple Endocrine Neoplasia 2 Syndrome -- Surgical treatment of medullary thyroid carcinoma -- Long term follow up in medullary thyroid carcinoma -- Use of Tyrosine Kinase Inhibitors for Treatment of Medullary Thyroid Carcinoma.